Analysis of Female Headmasters in West Sumatra - Yuliarti, Sesrita; Fatmariza, Fatmariza; Montessori, Maria (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to analyze the leadership of women as principals. The Leadership was observed in the terms of nature, behavior, situation, strengths, weaknesses, opportunities, and challenges of women's leadership. The study used a qualitative approach with case studies. Furthermore, purposive sampling was used to determine the participants of the research. Data were collected through observation, interview and documentation. Validation of the data was done through data reduction, data presentation and data verification. The results of the research, in terms of the leadership of the principal, show that the principals have the ability and readiness of knowledge. From the behavioral aspect, the principals can establish good relationship which is familial and democratic. Therefore, the leadership situation of female principals creates a humane and democratic atmosphere. The advantages of female principals are seen in terms of emotional stability, awareness, communicative, detail and confidence, however, there are still weaknesses in terms of assertiveness, with strong patriarchal values. Nevertheless, female principals still can work in the public sphere by attending training and becoming organizational officials. Female principals face more challenges not only to advance the school but to provide good leadership proof in order to reduce the paradigm of ideal male leader. It can be concluded that the female principals’ leadership is able to provide a new, democratic, and humanist ambience. Keywords: democratic, humanistic, female leadership ABSTRAK Penelitian ini bertujuan menganalisis kepemimpinan perempuan sebagai kepala sekolah. Ditinjau dari segi sifat, perilaku, situasi, kekuatan, kelemahan, kesempatan, dan tantangan kepemimpinan perempuan. Penelitian menggunakan pendekatan kualitatif dengan studi kasus. Selanjutnya purposive sampling untuk menentukan informan penelitian. Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Keabsahan data melalui reduksi data, penyajian data dan verifikasi data. Hasil penelitian dari sifat kepemimpinan kepala sekolah menunjukkan kesanggupan dan kesiapan pengetahuan melalui pelatihan. Seterusnya segi perilaku mampu menjalin hubungan bersifat kekeluargaan, demokratis. Dengan demikian situasi kepemimpinan perempuan menciptakan suasana humanis dan demokratis. Terlihat kelebihan kepemimpinan perempuan dari sisi kestabilan emosi, kepedulian, komunikatif, detail dan percaya diri, namun masih terdapat kelemahan segi ketegasan terutama disekolah kejuruan dengan nilai-nilai patriarkhis. Meskipun demikian kepemimpinan perempuan memiliki peluang bekerja diruang public. Perempuan menghadapi banyak tantangan memberikan pembuktian kepemimpinan ideal. Dapat disimpulkan kepemimpinan kepala sekolah perempuan mampu memberikan nuansa baru demokratis dan humanis dalam kepemimpinannya. Kata kunci: demokratis, humanis, kepemimpinan perempuan